Wireless poly(dimethylsiloxane) quartz-crystal-microbalance biosensor chip fabricated by nanoimprint lithography for micropump integration aiming at application in lab-on-a-chip. (8th June 2018) - Kato, Fumihito; Noguchi, Hiroyuki; Kodaka, Yukinari; Oshida, Naoya; Ogi, Hirotsugu
Abstract: We developed a quartz-crystal-microbalance (QCM) biosensor chip that operates wirelessly via electromagnetic waves, using poly(dimethylsiloxane) (PDMS). An AT-cut quartz oscillator (22–30 µm) is packaged in a microchannel, where it is supported by micropillars without mechanical fixing. As a result, the quartz oscillator is little affected by the thermal stress caused by the difference in the thermal expansion coefficients of the components, and the leakage of the vibration energy of the quartz oscillator is reduced. Consequently, high-frequency (∼56 MHz) measurement with a stable baseline (±∼2 ppm) is realized. We succeeded in repeatedly monitoring the binding reaction between immunoglobulin G (IgG) and Staphylococcus aureus protein A (SPA) with the quartz oscillator on which SPA molecules were immobilized nonspecifically. In addition, the affinity between SPA and IgG was calculated from the association and dissociation curves, and the usefulness of our wireless PDMS QCM biosensor was demonstrated.